Job Demands and Resources Perceived by Dentists in a Digital Dental Workplace and Perceived Effects on Job Satisfaction and Stress: A Qualitative Study - Julia Sofie Gebhardt; Volker Harth; David A. Groneberg; Stefanie Mache (Clinics and Practice)
Background: Digitalisation is becoming increasingly integrated into the field of dentistry; therefore, it is crucial to understand both the challenges it introduces and the opportunities it provides. By doing so, the research will offer insights into how digital tools can affect the work environment and contribute to the overall well-being and performance of dental professionals. Objectives: The present study aims to explore how dentists perceive the demands and resources within a digitalised dental practice. Methods: The present study adopted a qualitative design, incorporating guideline-based interviews. A total of 30 interviews were conducted with dentists from various German dental practices, with a focus on key topics such as job demands, job resources, digital stress factors, job satisfaction, and support needs in the context of digital dentistry. The interview data were analysed using qualitative content analysis. Results: The findings highlight that digital systems in dental practices offer benefits such as reduced errors and time savings, but also pose challenges, especially for less experienced users. While they improve efficiency, precision, and professional development, they can also lead to negative effects like dependence on technology, loss of manual skills, technical failures, and increased stress, particularly during the adaptation phase. These results suggest that successful integration of digital technologies requires adequate support to overcome initial learning curves and ensure long-term benefits. Conclusions: The results of the study underline the importance of effective implementation, comprehensive staff training, and technological reliability to maximise the benefits of digital tools and minimise their drawbacks. Maintaining a balance between digital stressors and resources is crucial to promoting a healthy work environment. Future research should focus on the long-term effects of training programmes and the integration of digital technologies into dental practices to increase their effectiveness in terms of job satisfaction and reduce potential risks.